Studi Literatur Penerapan E-Banking Syariah Pada Sistem Informasi Manajemen Perbankan Syariah - Purba, Fitri Annisa; Amri, Muhammad Khairul; Chairina, Chairina (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2023)
This study aims to understand the implementation of Islamic internet banking in Islamic banking management information systems based on selected literature. The results of this study are related to the Islamic online banking literature on information systems that are currently developing using products in digital form, namely in the form of devices or smartphones in the palm of your hand. The research design was carried out by collecting certain literature from Scopus data and carrying out a literature search on research materials. The research results include 10 articles that validate the application of electronic banking in bank management. In its operations, Islamic Banking participates with IT knowledge working to form an Islamic banking information system in order to create specific applications to facilitate all methods of banking transactions. This study recommends that future research should further improve information technology in bank management, especially Islamic banks.